Evaluation of the superplasticizer effect on the workability and strength of concrete - Alsadey, Salahaldein; Mohamed, Saieed (International Journal of Engineering and Technology, 2020)
The adverse effects of temperature on the properties of fresh concrete include increased water demand, shorter setting time and increased slump loss. Superplasticizer (SP) is important for enhancing the workability and setting time of concrete in hot weather. Hence, an experi-mental investigation was conducted to determine the optimum dosage of an admixture and to study the effect of over dosing this admixture. Concrete mixes with SP dosages of 0.8%, 1% and 1.2% by weight of cement were prepared along with a control mix (water/cement ratio of 0.55). After casting, the concrete samples underwent normal curing. Among the properties of fresh concrete determined were compressive strength as well as workability. The over dosage of SP appeared to degrade the properties of concrete with an indication of lower compres-sive strength. However, if the dosage levels are lower than the optimum dosage, raising the admixture dosage might help enhance the con-crete characteristics.Â